Addressing Geriatric Oral Health Concerns through National Oral Health Policy in India - Abhinav Singh; Bharathi M Purohit (Kerman University of Medical Sciences, 2015)
There is an escalating demand for geriatric oral healthcare in all developed and developing countries including India. Two-thirds of the world's elderly live in developing countries. This is a huge population that must receive attention from policy-makers who will be challenged by the changing demands for social and health services including oral health services. Resources are limited thus rather than being aspirational in wanting to provide all treatment needed for everybody, this critique presents a road map of how we might answer the present and future geriatric oral health concerns in a most efficient manner in a developing country. Viewing the recent Indian demographic profile and the trends in oral health, pertinent policy subjects have been discussed concerning the oral health needs of the elderly and also the associated challenges which include strategies to improve quality of life, strategies to train and educate the dental workforce and above all the role of healthcare systems towards realization of better aged society in India and other developing countries